Dark Adaptometry Kinetics Differentiates Age-Related Macular Degeneration from Central Serous Chorioretinopathy - Ashwin P. Verghese, BE; Claudia C. Lasalle, BA; David J. Ramsey, MD, PhD (Ophthalmology Science, 2025)
Purpose: To assess the diagnostic utility of dark adaptometry (DA) rod intercept time (RIT) to differentiate age-related macular degeneration (AMD) from central serous chorioretinopathy (CSCR). Design: Retrospective consecutive case series. Participants: Consecutive patients with a clinical diagnosis of AMD or CSCR who were ≥50 years of age. Methods: The study included patients who had completed a DA study in ≥1 eye measured at 5° superior to the fovea on the retina. All patients underwent a comprehensive retina examination, including OCT assessment of the macula. Main Outcome Measures: Patients were classified based on their RIT, with an RIT >6.50 minutes considered a delay. Results: The study included 67 patients with AMD and 25 with CSCR. Patients with AMD tended to be older (73.8 ± 8.9 years vs. 65.0 ± 7.2 years, P < 0.001) and were more likely female (53.7% vs. 28.0%, P = 0.049) compared with their CSCR counterparts. Additionally, patients with AMD tended to exhibit poorer vision in both their better-seeing (logarithm of the minimum angle of resolution 0.14 ± 0.13 vs. 0.08 ± 0.13, P = 0.057) and worse-seeing (logarithm of the minimum angle of resolution 0.48 ± 0.47 vs. 0.26 ± 0.25, P = 0.028) eyes. Rod intercept times were slower in patients with AMD compared with CSCR, both in the faster-adapting (12.44 ± 6.96 minutes vs. 4.01 ± 1.28 minutes, P < 0.001) and slower-adapting (13.06 ± 6.67 minutes vs. 4.95 ± 1.78 minutes, P < 0.001) eyes. Using a delayed RIT in the faster-adapting eye to classify patients with AMD versus CSCR showed excellent performance with a sensitivity of 79.1% (95% confidence interval [CI]: 67.4%–88.1%) and perfect specificity of 100.0% (95% CI: 86.3%–100.0%), yielding an accuracy of 97.4% (95% CI: 91.7%–99.6%). After adjusting for age, sex, and visual acuity, RIT in the faster-adapting eye remained an independent predictor of AMD versus CSCR. Conclusions: Prolonged dark adaptation, indicated by a longer RIT, is capable of distinguishing individuals with AMD from CSCR, 2 conditions that share similar fundus features. Future investigations are warranted to assess the effectiveness of this noninvasive technique for AMD screening. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.